Subsequent memory effect in the inferior frontal gyrus revealed by fNIRS - Petra Bíró; Silvy H. P. Collin (PLoS ONE, 2026)
A central finding in memory research is the subsequent memory effect, which describes consistent neural differences during encoding, where later remembered events elicit higher brain activity than those that are later forgotten, which has been reliably replicated with both EEG and fMRI for the past decades. Replicating the subsequent memory effect using fNIRS could enable research opportunities that are difficult to pursue with other methods, including studies with children, patient populations, or experiments in highly naturalistic settings. Therefore, our study investigated whether the prefrontal cortex is differentially involved in subsequently remembered versus subsequently forgotten stimuli using fNIRS. Our results showed that in particular channels mapping onto the inferior frontal gyrus showed more activation during encoding of subsequently remembered events compared to subsequently forgotten events. These results demonstrate that fNIRS can reliably capture the subsequent memory effect, providing new opportunities to study memory mechanisms across diverse populations and real-world contexts.